Integrating steganography for enhancing security in banking business processes - Umanskiy, Oleksandr (National Technical University "Kharkiv Polytechnic Institute", 2024)
This paper investigates novel methodologies to bolster the security of banking business processes amidst escalating cyber threats. Focused on the integration of steganographic techniques, particularly digital watermarks, the study aims to fortify the confidentiality and integrity of sensitive information transmitted within banking operations. Through comprehensive analysis and experimental validation, this research contributes to advancing the understanding of steganography's efficiency in enhancing traditional encryption methods within the banking sector.
Keywords: steganography; digital watermarks; banking security; data transmission; cybersecurity